Adult Colo-Colic Intussusception Induced By a Lipoma Masquerading As a Sigmoid Polyp on Colonoscopy: A Case Report - Nabi, Junaid; Akhter, SM Quamrul; Al Mamun, Mohammad Abdullah; Jahan, Nelema; Rahman, Md Mamunur (Journal of Shaheed Suhrawardy Medical College, 2013)
Intussusception in adults is rare, accounting for only 5% of all cases of intussusceptions and only 1% of bowel obstruction. Preoperative diagnosis is often difficult due to non specific symptoms and subacute nature. This case report was a per-operatively diagnosed adult colo-colic intussusception induced by a lipoma which mimicked a sigmoid polyp on colonoscopy. A 40-year-old Bengali woman was admitted with two weeks history of colicky lower abdominal pain. Ultrasound abdomen was unremarkable. Colonoscopy revealed a moderately enlarged sigmoid polyp at 25 cm from the anal verge. A midline incision laparotomy was performed only to reveal a colo-colic intussusception. The intussusception was reduced and the patient underwent a segmental resection of the involved bowel. Histological evaluation confirmed the diagnosis of lipoma of the colon. The patient however satisfactory recovery and remains well six months after surgery. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16226 J Shaheed Suhrawardy Med Coll, 2013;5(1):72-74